Culture et changement urbain dans les Quartiers Sud de Buenos Aires (Argentine) : des arènes ambiguës - Barbara Morovich (IdeAs)
This article analyzes «cultural arenas» in the Southern Neighborhoods of Buenos Aires. Since 2008, the establishment of creative or economic clusters has accompanied a phenomenon of gentrification. The ambiguity of the concept of culture and its uses allows appropriations in defense of different issues, sometimes divergent ones. This work focuses on the liveliness of these arenas, the patience of their actors, their resistance, their ability to slow down the process of gentrification, through long-term challenges. Three examples are developed: San Telmo, La Boca and Piedrabuena. In these neighborhoods, projects linked or in conflict with institutions, are vectors of identity and patrimonialization and sometimes act against stigma, in the name of art and culture.